2022
DOI: 10.21203/rs.3.rs-2239682/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Three-month Antibody Persistence of a Bivalent Omicron-containing Booster Vaccine Against COVID-19

Abstract: We previously presented day 29 interim safety and immunogenicity results from a phase 2/3 study comparing the Omicron-BA.1-containing bivalent vaccine mRNA-1273.214 (50-µg) to the 50-µg mRNA-1273 booster in adults who previously received the mRNA-1273 primary series (100-µg) and mRNA-1273 first booster (50-µg) dose. Here we present day 91 post-booster results. Participants were sequentially enrolled to receive 50-µg of mRNA-1273 (n = 376) or mRNA-1273.214 (n = 437) as second booster doses. In participants with… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 11 publications
3
26
0
Order By: Relevance
“…5,[9][10][11][12] The BA.1 bivalent vaccine was well-tolerated and increased the magnitude and the durability of the neutralizing antibody responses against BA.1 compared to the original booster mRNA-1273. 5,6 Additionally, mRNA-1273.214 exhibited cross-neutralization ability against omicron BA.4/BA.5, BA.2.75 and other variants. 5,6 An omicron BA.4/BA.5 bivalent booster (mRNA-1273.222) has been authorized in the United States and elsewhere for the fall 2022 immunization campaign.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…5,[9][10][11][12] The BA.1 bivalent vaccine was well-tolerated and increased the magnitude and the durability of the neutralizing antibody responses against BA.1 compared to the original booster mRNA-1273. 5,6 Additionally, mRNA-1273.214 exhibited cross-neutralization ability against omicron BA.4/BA.5, BA.2.75 and other variants. 5,6 An omicron BA.4/BA.5 bivalent booster (mRNA-1273.222) has been authorized in the United States and elsewhere for the fall 2022 immunization campaign.…”
Section: Introductionmentioning
confidence: 96%
“…5,6 Additionally, mRNA-1273.214 exhibited cross-neutralization ability against omicron BA.4/BA.5, BA.2.75 and other variants. 5,6 An omicron BA.4/BA.5 bivalent booster (mRNA-1273.222) has been authorized in the United States and elsewhere for the fall 2022 immunization campaign. 13 Early effectiveness data demonstrate that recipients of an omicron-containing bivalent booster have improved protection against Covid-19 relative to immunization with the original mRNA-1273 vaccine only.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…To this end, S-specific antibodies and T-cells will be measured and compared on day 7 and 28 post boost. Clinical trials involving bivalent vaccines thus far only measured neutralizing antibodies at day 28 after the booster ( 15 , 22 ). The analysis of the response at day 7 has two advantages: i) rapid recall responses after vaccination could be a proxy for recall upon infection, indicative of whether booster vaccinations are required or not, and ii) early immunogenicity evaluation can accelerate the interpretation of future studies.…”
Section: Outcomementioning
confidence: 99%
“…Bivalent vaccines that contain both the ancestral S protein, to boost previously induced immune responses, and the Omicron BA.1 or BA.5 S protein, to specifically boost antibodies recognizing viruses from the Omicron sub-lineage, have been designed for that reason. A study on one bivalent vaccine reported superiority in the induction of neutralizing antibodies to omicron sub-lineage variant BA.1 compared to the previously approved monovalent vaccine ( 15 ). Although the seasonality of SARS-CoV-2 outbreaks has not been determined yet and varies across different climates, more frequent surges have been observed in colder months ( 16 ).…”
Section: Introductionmentioning
confidence: 99%